Escola e questão racial: a avaliação dos estudantes - Silva, Rutinéia Cristina Martins [UNESP] (2013)
The theme of this research, which resulted in the preparation of doctoral dissertation is racial prejudice and the issues that surround the school environment. In this sense, the goal of guiding the preparation of this work is to investigate how students enrolled in grade 5/6 th grade elementary school work evaluated regarding the race issue. In this work, it is racial question the relationship between the various racial and ethnic groups, focusing on the social damage suffered by the descendants of African peoples which looks black and not just cultural characteristics of this ethnic group as the majority of the Brazilian people. At school, are placed two foci: the teaching of history and African and Afro-Brazilian culture and conflict resolution arising from differences and racial prejudice, so that these two foci arise the questions used in the interviews with students, teachers and managers of History school. To conduct the study, we built a theoretical framework that allowed us to know aspects of the history of race relations in Brazil in the period after the abolition of slavery on May 13, 1888, which includes the knowledge of how legislation conceived the black person as the black social movement organized itself in defense of the rights of black people, which resulted in policies such as affirmative action and the Law 10.639/2003. This theoretical framework was constructed under a historical materialist perspective, which takes into account the historical conditions experienced by individuals and the influence of the material conditions of the society in which they live. To achieve the results we conducted a field survey, based on institutional documents and proposed government education, which was completed the analysis from the answers given in the interviews. Such responses were analyzed with reference to the method of content analysis. After analyzing the results, it was possible to draw a picture of how is the training of...